BAGAIMANA MENCIPTAKAN KINERJA KARYAWAN YANG EFEKTIF PADA PERUSAHAAN JASA? (Study of Printing Companies in Malang City) - Yogatama, Ahmad Nizar; Yulianto, Lutfy Marita (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2020)
The development of various kinds of businesses in the city of Malang that is so fast becomes one of the bases for printing companies to develop businesses because many of these businesses require services for brochures, logos and so forth. This business development requires an increase in employee performance because employees become the main movers of service companies, especially in the CV. Intidesign. This research uses a quantitative approach to the type of causal research. The population in this study were employees of CV. Intidesign Malang, with saturated sampling technique where all existing populations are used as samples, that is, 40 respondents. Analysis of the data used in this study is multiple regression analysis. From the results of the study suggested CV. Intidesign Malang is expected to continue to pay attention to the physical work environment around employees who carry out work and implement a good workload distribution to improve employee performance. Future researchers who are interested in reviewing employee performance are expected to develop research results through taking variables that have an influence on employee performance and the selection of different objects. Thus, it can help enrich the results associated with factors that can affect employee performance.